Pottery‐Inspired Flexible Fire‐Shielding Ceramifiable Silicone Foams for Exceptional Long‐Term Thermal Protection - Chen, Zuan‐Yu; Wu, Yu‐Yue; Liu, Shuai‐Chi; Li, Yang; Guan, Zi‐Qi; Cao, Cheng‐Fei; Zhang, Guo‐Dong; Tuten, Bryan T.; Gao, Jie‐Feng; Shi, Yong‐Qian; Song, Pingan; Tang, Long‐Cheng (Advanced functional materials, 2025)
Owing to their preeminent properties, including mechanical flexibility, thermal insulation, and low cost, silicone foams are widely used in industrial fields. However, flame‐induced structural failure greatly restricts their practical applications. It is challenging for flexible silicone foams to realize reliable thermal protection in thermo–mechanical–oxidative environments. Inspired by traditional pottery, a multiscale‐filler synergistic ceramifiable strategy for creating silicone foam nanocomposites with flexibility and long‐term fireproofing is proposed herein. The foam materials not only maintain mechanical flexibility and elasticity (≈2% residual strain after 1000 cycles) at a temperature range of −60–210 °C but also exhibit exceptional long‐term (>30 min) thermal insulation upon exposure to ≈1300 °C oxidative environments because of their ability to form a gradient robust porous ceramic structure. Moreover, the foam material can provide stable thermal protection for electric cables and lithium‐ion battery packs, making it one of the most reliable thermal insulation materials so far. This work broadens the applications of silicone foams in emerging fields where mechanical buffering and fireproofing are required. Pottery‐inspired ceramifiable silicone foam nanocomposites are designed. The nanocomposites exhibit mechanical flexibility and elasticity over wide temperature ranges, but can yield a gradient porous ceramic structure upon exposure to high temperatures, showing long‐term fireproof performance. This strategy provides a promising material system for emerging fields in which mechanical buffering and fireproofing are required, such as new electric vehicles.